Optimizing Childcare through the Role of Fathers from the Perspective of Maqashid Syariah - Ikromi, Zul; Safrizal, Safrizal (Jurnal El-Thawalib, 2026)
Childcare is a crucial aspect in shaping a child's character, morals, and psychological development. In social practice, the responsibility for childcare is often placed more heavily on the mother, while the father's role is often understood only as a breadwinner. This creates a gap between the ideal concept of the family in Islam, which emphasizes the shared responsibility of parents in educating and nurturing children. Therefore, this study aims to analyze the optimization of childcare through the father's role from the perspective of the maqashid sharia (objectives of sharia) as a normative framework for comprehensively realizing children's welfare. This study is a qualitative library research with both normative and maqashid sharia approaches. The primary data sources in this study are verses of the Qur'an, the Prophet's hadith, and primary literature discussing the concept of childcare and maqashid sharia. Meanwhile, secondary data sources include classical and contemporary fiqh books, academic books, scientific journals, and research works relevant to the theme of the father's role in childcare. The data collection technique involves a literature review, tracing, reviewing, and classifying relevant written sources. The data were then analyzed using qualitative descriptive methods, including content analysis and conceptual analysis grounded in the maqashid sharia. The results of the study indicate that optimizing fathers' role in childcare is an important part of realizing the goals of sharia, especially in maintaining religion (hifz al-din), protecting the soul (hifz al-nafs), protecting the mind (hifz al-‘aql), and protecting offspring (hifz al-nasl). The active involvement of fathers in education, moral development, and emotional support for children can strengthen the quality of parenting and help create harmonious families and a generation with morals and responsibility.